Utilization of waste heat recovery from air conditioning system for clothes drying application - Yaakop, Sharul Nizam (2025)
Air conditioning (AC) systems are designed to regulate indoor air quality and provide thermal comfort. In a conventional vapor compression cycle system (VCCS), a considerable amount of waste heat is released from the condenser unit. This study focused on recovering this waste heat to be reused in an air dryer prototype for clothes drying purposes, targeting improved energy efficiency and drying performance. The methodology was carried out in three main phases. The first phase involved the identification and modelling of critical elements in the heat rejection process from the VCCS, with drying time set as the model output. A model was then integrated and validated based on predicted drying time. The second phase included the development of an actual prototype based on the model design, followed by experimental testing. Data were collected by varying several parameters such as ambient dry-bulb temperature, clothes mass (1950 g, 4255 g, and 6350 g), and condenser fan speed. These data were analyzed to verify whether the performance fulfilled the modeled expectations. In the final phase, the collected data were analyzed using COOLPACK 1.49 software to evaluate key performance indicators. The validation was conducted based on achieving a coefficient of performance (COP) greater than 2.5 and a drying time below 120 minutes. The experimental results successfully showed that clothes were dried within 55 to 110 minutes, depending on load size, using air expelled at a flow rate of 0.34 m³/s in a 33°C environment. The integration of the heat recovery system improved the COP from 2.36 to 2.70 (14.4%). This study demonstrated that an HVAC-based heat recovery system is a viable and energy-efficient alternative to conventional electric dryers by utilizing waste thermal energy, leading to reduced electricity consumption and improved system performance.